Electrostatic self-assembly: understanding the significance of the solvent - Lindgren, Eric B.; Derbenev, Ivan N.; Khachatourian, Armik; Chan, Ho-Kei; Stace, Anthony J.; Besley, Elena (American Chemical Society, 2018)
The electrostatic deposition of particles has become a very effective route to the assembly of many nanoscale materials. However, fundamental limitations to the process are presented by the choice of solvent, which can either suppress or promote selfassembly depending on specific combinations of nanoparticle/surface/solvent properties. A new development in the theory of electrostatic interactions between polarizable objects provides insight into the effect a solvent can have on electrostatic self-assembly. Critical to assembly is the requirement for a minimum charge on a surface of an object, below which a solvent can suppress electrostatic attraction. Examples drawn from the literature are used to illustrate how switches in behavior are mediated by the solvent; these in turn provide a fundamental understanding of electrostatic particle-surface interactions applicable to many areas of materials science and nanotechnology.